2006
DOI: 10.1007/s00484-006-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of solar radiation on thermal comfort

Abstract: The aim of this study was to investigate the relationship between simulated solar radiation and thermal comfort. Three studies investigated the effects of (1) the intensity of direct simulated solar radiation, (2) spectral content of simulated solar radiation and (3) glazing type on human thermal sensation responses. Eight male subjects were exposed in each of the three studies. In Study 1, subjects were exposed to four levels of simulated solar radiation: 0, 200, 400 and 600 Wm(-2). In Study 2, subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(74 citation statements)
references
References 22 publications
1
64
1
3
Order By: Relevance
“…Traditional approaches to estimating R in outdoor thermal comfort research can be time-consuming, expensive, cumbersome, and may not adequately address the contribution of the short-and long-wave radiation fluxes on the human body (Hodder and Parsons 2007;La Gennusa et al 2005). Although R can be modeled based on planar measurements of incoming and outgoing short-and long-wave radiation fluxes, readily available radiation data can often be difficult to obtain, as the incoming and outgoing solar and terrestrial radiation fluxes are not all commonly observed variables at many meteorological stations, and the equipment used to make these measurements is costly and highly specialized (Baigorria et al 2004;Gul et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional approaches to estimating R in outdoor thermal comfort research can be time-consuming, expensive, cumbersome, and may not adequately address the contribution of the short-and long-wave radiation fluxes on the human body (Hodder and Parsons 2007;La Gennusa et al 2005). Although R can be modeled based on planar measurements of incoming and outgoing short-and long-wave radiation fluxes, readily available radiation data can often be difficult to obtain, as the incoming and outgoing solar and terrestrial radiation fluxes are not all commonly observed variables at many meteorological stations, and the equipment used to make these measurements is costly and highly specialized (Baigorria et al 2004;Gul et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The subjective experiments were carried out on a chamber in order to develop the driver's fatigue model. Hodder and Parsons (2007) have investigated the relation between simulated solar radiation and thermal comfort. In this work, three effects were studied, (1) the intensity of direct simulated solar radiation, (2) spectral content of simulated solar radiation and (3) glazing type on human thermal sensation responses.…”
Section: Introductionmentioning
confidence: 99%
“…Hodder and Parsons ('H/P') used an automobile mockup ( Figure 6) with moveable heat lamps to emulate four levels of solar radiation impinging on human subjects [8]. Air temperature was between 22.8 and 24.0°C, metabolic rate 1.2 met, and clothing resistance 0.7 clo.…”
Section: Comparing Model Predictions To a Human Subject Testmentioning
confidence: 99%
“…Although Fanger published projected area factors for the human body in 1970 [7], the subject of shortwave gain and comfort has been almost absent from the research literature until recently. A few studies [8,9,16,19] have addressed the effect of solar heating on comfort.…”
mentioning
confidence: 99%